Tau and Amyloid-β Peptides in Serum of Patients With Parkinson's Disease: Correlations With CSF Levels and Clinical Parameters - Schirinzi, Tommaso; Zenuni, Henri; Grillo, Piergiorgio; Bovenzi, Roberta; Guerrera, Gisella; Gargano, Francesca; Pieri, Massimo; Bernardini, Sergio; Biagio Mercuri, Nicola; Battistini, Luca; Sancesario, Giulia Maria (Frontiers in Neurology, 2022)
Relevance of blood-based biomarkers is increasing into the neurodegenerative diseases field, but data on Parkinson’s disease (PD) remain still scarce. In this study, we used the SiMoA technique to measure serum content of total tau protein and amyloid-β peptides (Aβ-42, Aβ-40) in 22 PD patients and ten control subjects. Serum levels of each biomarker were correlated with the respective CSF levels in both the groups; in PD patients, also the correlations between serum biomarkers and main clinical parameters were tested (motor, non-motor, cognitive scores and levodopa equivalent daily dose). Serum biomarkers did not exhibit quantitative differences between patients and controls; however, only PD patients had inter-fluids (serum-CSF) associations in tau and amyloid-β-42 levels. Moreover, serum content of tau protein was inversely correlated with cognitive performances (MoCA score). These findings, although still preliminary, indicate that brain-derived peptides change in peripheral blood of PD patients in parallel to CSF, even in association with some clinical feature. Further studies are now needed to validate the use of blood-based biomarkers in PD.